PHILOSOPHY OF SCIENCE ANALYSIS IN STUDIES RELATED TO CLIMATE CHANGE IMPACTS ON THE RESILIENCE OF INFORMAL AREAS - Adnin Musadri Asbi; Diyanti Isnani Siregar (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
Climate change is a topic of discussion in various parts of the world. Several coastal cities in Indonesia are currently also threatened by the impacts of climate change. From several studies, it is known that the threat of climate change is considered capable of increasing community resilience in informal areas. This study aims to identify the application of the principle of verification of positivism and its implications as an analysis of the philosophy of science in the study of climate change impacts on the resilience of informal areas. The analytical technique used is descriptive evaluative by using several literature reviews and theories. From the results of the study, it was found that research related to climate change and resilience of informal areas is an empirical, logical, and measurable research as well as part of a deductive research and reflects that the theme of this research is a part of science.